الأحكام المستحدثة لهيئات المشاركة و الطعن و الحوار في القانون الجزائري - جـــلالـــي ،هــشــــــام; عـبـيـد،زين العابدين (جامعة الوادي University of El Oued, 2024)
ان المشرع من خلال نصه على العديد من المسائل المستحدثة في هيئات المشاركة والطعن والحوار في نطاق الوظيفة العمومية من خلال النصوص القانونية الصادرة في هذا الشأن، ساهم في تعزيز اليات المشاركة و الحوار الاجتماعي كوسيلة لتبني حلول مشتركة وتوافقية تساهم في تحسين الظروف العامة للعمل وترسى أسس الاستقرار المهني والاجتماعي وحلولا لجميع الوضعيات المتعلقة بالعلاقات الاجتماعية والمهنية للموظف في المؤسسات والإدارات العمومية ، وبهذا يكون قد ساهم في ضمان سير المرافق العمومية للدولة بانتظام واضطراد وتحسين الخدمة العمومية . The legislator, through its provisions on various newly introduced issues concerning participation, appeals, and dialogue within the scope of public employment as stipulated in the relevant legal texts, has contributed to enhancing mechanisms of participation and social dialogue as a means to adopt joint and consensual solutions. These mechanisms help improve the general working conditions and establish the foundations for professional and social stability. They also provide solutions for all situations related to social and professional relations of employees in public institutions and administrations. In doing so, the legislator has contributed to ensuring the regular and consistent operation of public facilities and improving public services.
ماستر اداري